Maropéen.nes. De l’altérisation à la négociation des appartenances - Rim Affaya (L’Année du Maghreb)
This article examines the ability of people of Moroccan descent living in Europe to produce an alternative imaginary through trade. While the question of the origin of individuals mobilizes political and academic attention to assess their degree of integration in host countries and their attachment to their country of origin, cultural and consumer practices are at work among individuals to overcome the othering they face in their daily lives. Through an economic anthropological approach to the world of marriage, its actors and its economy, this article presents an analysis of a new service in Europe. The tangaft, as an accompaniment service for Moroccan weddings, brings together individual and collective experiences that reveal how certain actors transcend the divide between origins and new citizenship by developing registers of representations that, instead of opposing each other, combine the multiple affiliations with which they identify. The moropeanity shows how plural identities are made both in the intimacies that are founded in marriage and in the development of business between Morocco and Europe.